1996
DOI: 10.1007/bf00195187
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular location of the tetrapyrrole synthesis enzyme porphobilinogen deaminase in higher plants: an immunological investigation

Abstract: A recombinant plasmid, pArab8, harbouring the cDNA encoding the mature form of the tetrapyrrole synthesis enzyme porphobilinogen deaminase (EC 4.3.1.8; also known as hydroxymethylbilane synthase) from Arabidopsis thaliana (L.) Heynh. has been constructed, and used to transform Escherichia coli. The porphobilinogen deaminase protein from Arabidopsis was overexpressed in this strain, and purified to homogeneity (3000-fold) with a yield of 20%. Antibodies were raised against the purified plant enzyme, and used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…RUG1 is broadly expressed, as shown by data deposited at different publicly available microarray databases [Genevestigator (https://www.genevestigator.com/gv/) and the BIO-array resource (BAR; http://bar.utoronto.ca/efp/cgi-bin/efpWeb.cgi)] and consistent with other experimental results that detected PBGD in different organs of Arabidopsis [41], [42] and pea [40]. Interestingly, we found that overexpression of Arabidopsis PBGD in a wild-type genetic background leads to the appearance of supernumerary shoot apical meristems and occasionally small necrotic patches in the leaves (Figure S2d–f).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…RUG1 is broadly expressed, as shown by data deposited at different publicly available microarray databases [Genevestigator (https://www.genevestigator.com/gv/) and the BIO-array resource (BAR; http://bar.utoronto.ca/efp/cgi-bin/efpWeb.cgi)] and consistent with other experimental results that detected PBGD in different organs of Arabidopsis [41], [42] and pea [40]. Interestingly, we found that overexpression of Arabidopsis PBGD in a wild-type genetic background leads to the appearance of supernumerary shoot apical meristems and occasionally small necrotic patches in the leaves (Figure S2d–f).…”
Section: Resultssupporting
confidence: 88%
“…In animals and yeast, PBGD is a cytosolic protein but in higher plants and algae, it is targeted to the chloroplast [40]. In Arabidopsis, PBGD is a chloroplast protein encoded by a single-copy gene [41], [42]. The overall sequence similarity between the PBGD of Arabidopsis and other organisms is moderately high: 76, 75, 74, 46, 38, 37, 37 and 35% identity for pea, wheat, rice, Escherichia coli , human, mouse, Danio rerio and Saccharomyces cerevisiae , respectively (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore used a precursor for another tetrapyrrole biosynthesis enzyme, porphobilinogen deaminase, which had previously been shown to be imported into pea chloroplasts (14) and which had been determined to be located exclusively within the plastids (30). Fig.…”
Section: Origin Of the Additional 38-kda Band After Protease Treatmenmentioning
confidence: 99%
“…Protogen oxidase activity has also been measured in plasma membrane [11,12] and endoplasmic reticulum [13], although this activity had different characteristics from those in the plastids and mitochondria. In contrast, all the steps up to and including coproporphyrinogen III oxidase are confined to plastids [9,[14][15][16], and it is likely that protogen IX is exported from these organelles to other subcellular locations. Evidence for the export of this compound was obtained after the incubation of isolated barley plastids with the tetrapyrrole precursor 5-aminolaevulinic acid [17].…”
Section: Introductionmentioning
confidence: 99%